Efficiency-Adjusted Public Capital, Capital Grants, and Growth - Crivelli, Ernesto (IMF Working Papers; Working Paper ;, 2017)
Recent literature has explored the relationship between efficiency-adjusted public capital and economic growth. A debate on whether capital grants, and especially EU funds actually contribute to growth has gained prominence lately. This paper empirically assesses the relationship between the quality of public investment, capital grants, and growth in a sample of 43 emerging and peripheral economies over 1991-2015. To this end, the contribution of public capital to growth is estimated using efficiency-adjusted public capital stock series, constructed reflecting the quality of public investment management institutions. In addition, the determinants of effective public investment are analyzed. The results suggest that capital grants contribute positively to effective public investment, and the latter is significant in explaining variations in economic growth. Finally, the paper illustrates the impact of raising EU funds absorption on potential growth in emerging and peripheral EU countries.